2023
DOI: 10.1002/wsb.1493
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lesser prairie‐chicken translocation through survival and lek surveys

Elisabeth C. Teige,
Liam A. Berigan,
Carly S. H. Aulicky
et al.

Abstract: Translocation is a management tool used to restore or augment wildlife populations, but outcomes of translocations are often poorly documented and can have varying levels of success for improving wildlife population declines. The lesser prairie‐chicken (Tympanuchus pallidicinctus) is a prairie grouse endemic to the southern Great Plains. In response to declining abundance and distribution, in 2023 lesser prairie‐chickens were listed as threatened or endangered under the Endangered Species Act in different stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Observed movements were >5 times longer than those measured in native populations (Earl et al, 2016) and likely contributed to mortality for translocated birds. Of all released birds, 13.1% died (n = 54) and 9.7% went missing (n = 40) within the first 2 weeks after release, indicating potentially substantial mortality associated with the act of translocation, adjustment to the new environment, and dispersal movement after translocation (Teige et al, 2023). High initial mortality rates are not unprecedented among prairie grouse translocations; Mathews et al (2022) found similar rates of mortality (0.992 daily survival) within the first 40 days after Columbian sharp-tailed grouse (Tympanuchus phasianellus columbianus) translocation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Observed movements were >5 times longer than those measured in native populations (Earl et al, 2016) and likely contributed to mortality for translocated birds. Of all released birds, 13.1% died (n = 54) and 9.7% went missing (n = 40) within the first 2 weeks after release, indicating potentially substantial mortality associated with the act of translocation, adjustment to the new environment, and dispersal movement after translocation (Teige et al, 2023). High initial mortality rates are not unprecedented among prairie grouse translocations; Mathews et al (2022) found similar rates of mortality (0.992 daily survival) within the first 40 days after Columbian sharp-tailed grouse (Tympanuchus phasianellus columbianus) translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Between fall 2016 and spring 2019, we translocated 411 lesser prairie‐chickens captured on leks to the Cimarron and Comanche National Grasslands using a hard release technique (not including measures that would facilitate a gradual transition to the release site; De Milliano et al., 2016). The initial fall 2016 release was primarily males (26 males, 1 female); all subsequent releases were in spring and had similar numbers of males and females (Berigan et al., 2022; Teige et al., 2023). We equipped birds translocated during fall 2016 and spring 2017–2019 with 11‐g bib‐style very‐high‐frequency (VHF) transmitters.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations